Efficacy of a calcium sucrose phosphate based toothpaste in elevating the level of calcium, phosphate ions in saliva and reducing plaque: A clinical trial - Leena Unnikrishnan Menon; R Balagopal Varma; Parvathy Kumaran; Arun Mamachan Xavier; Bhat Sangeetha Govinda; J Suresh Kumar (Wolters Kluwer Medknow Publications, 2018)
Aim: To evaluate and compare the efficacy of "calcium sucrose phosphate" (CaSP) toothpaste (Enafix 5%) with ordinarily used calcium, phosphate-containing toothpaste in elevating the level of calcium, phosphate ions in saliva. Secondary aims were to evaluate substantivity and plaque-reducing ability of CaSP toothpaste. Materials and Methods: Thirty study participants of age group 6-13 years were divided into two groups: Group X (Control group) was made to continue brushing with their regularly used calcium, phosphate-containing toothpaste and Group Y (Test group) was allotted CaSP toothpaste. 1 ml of unstimulated saliva was periodically collected from both groups to determine any alteration in the salivary calcium, phosphate level. Parameters such as substantivity and plaque-reducing ability of CaSP toothpaste were also evaluated. Salivary mineral's intergroup comparison was evaluated by Student's t-test while its intragroup comparison along with the plaque amount variation in Group Y was evaluated by ANOVA and Tukey's post hoc test. Results: Group Y showed an increase in the salivary calcium level though not statistically significant. The increase was pronounced in samples collected on day 1. Group Y showed a consistent level of calcium, phosphate in samples collected immediately and 6 h postbrushing, indicating its substantivity. In addition, Group Y had an impact in reducing the plaque level when the 1st-month plaque score was compared with the 12th-month score. Conclusion: CaSP leads to an increase in the salivary calcium level though it was not statistically significant. Supervised brushing and dietary habits showed a positive effect on both the groups. CaSP toothpaste also showed substantivity and plaque-reducing ability.